Factors influencing consumer purchase intention among people living in Phnom Penh: a study of Aliexpress cross-border e-commerce - Chhay Ly; Soun Hong (Southeast Asian Journal of Service Management, 2026)
In today’s digital age, cross-border e-commerce has significantly transformed consumer shopping behaviour by enabling access to global markets. However, consumers still encounter various challenges when engaging with these platforms. This study aims to examine the key factors influencing consumer purchase intention and to identify the major challenges faced by consumers in Phnom Penh when using cross-border e-commerce, particularly AliExpress. A quantitative research approach was employed, with data collected from 388 respondents through a structured questionnaire. Statistical analysis using SPSS was conducted to evaluate the effects of six factors: Trust on Platform, Perceived Usefulness, Purchase Behaviour, Perceived Security, Perceived Reliability on Logistics and Delivery, and Consumer Behaviour. The findings reveal that Trust on Platform, Perceived Usefulness, Perceived Reliability on Logistics and Delivery, and Consumer Behaviour have a significant influence on consumer purchase intention. In terms of challenges, product-related issues emerged as the primary concern, followed by shipping problems. Interestingly, around 40% of respondents reported experiencing no major challenges when engaging in e-commerce. These findings provide valuable insights for businesses and practitioners seeking to strengthen their presence in Cambodia’s cross-border e-commerce market by improving trust, logistics reliability, and overall customer experience.